Does Climate Change Influence Convergence in Indonesia? Spatial Approach - Hidayat, Muhammad; Sandri, Siti Hanifa; Murialti, Neng; Darwin, Ranti (International Journal of Energy Economics and Policy, 2025)
This study examines the nexus between climate change and regional economic convergence in Indonesia using panel data from 34 provinces (2011-2024). Employing the Spatial Durbin Model (SDM), the analysis explicitly captures spatial spillovers across regions. Results confirm conditional β-convergence with a relatively slow rate of 1.02% per year. Climate variables are critical: temperature and precipitation both exhibit inverted U-shaped relationships with growth, indicating that moderate levels support development while extremes become detrimental. Spatial spillovers reveal that severe weather shocks in neighbouring provinces significantly hinder convergence in the region of origin. Conversely, investment shows strong direct and indirect positive effects, while population growth slows convergence, and human capital contributes modestly. Overall, the findings highlight that climate dynamics shape not only local growth trajectories but also interregional interdependencies. The study provides new evidence for developing economies and offers policy insights for inclusive, low-carbon, and climate-resilient regional development.